Recurrence Patterns and Prognostic Factors in Patients with Hepatocellular Carcinoma in Noncirrhotic Liver: A Multi-Institutional Analysis - Arnaoutakis, Dean J. (2014)
BACKGROUND: Hepatocellular carcinoma (HCC) primarily affects patients with a cirrhotic liver. Reports on the characteristics of patients with HCC in noncirrhotic liver, as well as predictors of recurrence and survival, are scarce. METHODS: Between 1992 and 2011, 334 patients treated for HCC in noncirrhotic liver were identified from three major hepatobiliary centers. Clinicopathological characteristics were analyzed and independent predictors of recurrence and overall survival were identified using Cox proportional hazards models. RESULTS: Median patient age was 58 years and 77 % were male. Most patients had a solitary (81 %) and poorly or undifferentiated tumor (56 %); median size was 6.5 cm. The majority of patients (96 %) underwent liver resection (microscopically negative margins in 94 %), whereas a few had transarterial chemoembolization or transplantation (4 %). Median recurrence-free survival (RFS) was 2.5 years, and 1- and 5-year RFS was 71.1, and 35 %, respectively. Elevated alkaline phosphatase levels [hazards ratio (HR) = 1.82], poor tumor differentiation (HR = 1.4), macrovascular invasion (HR = 2.18), and the presence of satellite lesions (HR = 1.9), or intrahepatic metastases (HR = 2.59) were independently associated with shorter RFS; in contrast, an intact tumor capsule independently prolonged RFS (HR = 0.46). Median overall survival was 5.9 years, and 1- and 5-year overall survival was 86.9, and 54.5 %, respectively. Tumor size ≥5 cm (HR = 2.27), macrovascular (HR = 2.72) or adjacent organ invasion (HR = 3.34), and satellite lesions (HR = 2.18) were independently associated with shorter overall survival, whereas an intact tumor capsule showed a protective effect (HR = 0.51). CONCLUSIONS: Following resection of HCC in the setting of no cirrhosis, more than one-half of patients were alive after 5 years. However, even among patients with no cirrhosis, recurrence was common. Factors associated with RFS and overall survival included tumor characteristics, such as tumor capsule, satellite lesions, and vascular invasion.